2019
DOI: 10.1155/2019/7275063
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital Mortality among Ischemic Stroke Patients in Gondar University Hospital: A Retrospective Cohort Study

Abstract: Introduction Ischemic stroke is the third leading cause of mortality in low-income countries and the sixth in Ethiopia. The aim of this study was to determine the rate and predictors of in-hospital mortality due to ischemic stroke in Gondar University Hospital. Methods The study was conducted from April 1, 2017, to May 15, 2017, at Gondar University Hospital. A census using retrospective cohort study design was conducted on medical records of adult patients with the diagnosis of ischemic stroke attending the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
4
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 31 publications
4
43
4
6
Order By: Relevance
“…In agreement with our findings, studies conducted in Hawassa 3 and the University of Gondar, 23 found that the cardio-embolic sub-type of ischemic stroke was the most common identified, indicating the dominance of the cardiac causes of ischemic stroke. There was no significant difference in the survival time among different types of stroke; the hazard of death among hemorrhagic stroke patients was 29% lower than patients who had an ischemic stroke.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our findings, studies conducted in Hawassa 3 and the University of Gondar, 23 found that the cardio-embolic sub-type of ischemic stroke was the most common identified, indicating the dominance of the cardiac causes of ischemic stroke. There was no significant difference in the survival time among different types of stroke; the hazard of death among hemorrhagic stroke patients was 29% lower than patients who had an ischemic stroke.…”
Section: Discussionsupporting
confidence: 92%
“…In our setting, the mean length of hospitalisation was found to be 5.6 days, which is comparable with other studies conducted by Temesgen et al (6.7 days) 11 and Desita and Zewdu (6 days). 34 Conversely, the mean length of hospital stay at FHSCH was shorter than the studies performed by Gedefa et al, 41 Gebreyohannes et al, 51 de Carvalho et al 52 and Walker et al, 45 which were 11.14, 11.55, 15.4 and 19 days, respectively.…”
Section: Discussionmentioning
confidence: 76%
“…4 ). Furthermore, the proportion of atrial fibrillation among stroke patients included in this study ranged from 1% [ 28 ] to 37% [ 23 ], and our meta-analysis revealed that one-tenth [10% (95%CI: 5–19)] of stroke patients had atrial fibrillation (Fig. 5 ).…”
Section: Resultsmentioning
confidence: 99%